2018
DOI: 10.1007/s10964-017-0805-2
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Continuity in Depression: The Importance of Time-Varying Effects, Maternal Co-morbid Health Risk Behaviors and Child’s Gender

Abstract: Intergenerational continuity in depressive symptoms is well established between mother and child, but there are still important facets of this relationship that are underexplored. We examine intergenerational continuity in depressive symptoms between mother–child dyads as a flexible function of child age and account for the potential moderating role of maternal co-morbid health risk behaviors. Using prospective, self-report data collected yearly from 413 mother–child dyads (210 mother–son dyads and 203 mother–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 120 publications
0
11
0
Order By: Relevance
“…Research into the environmental causes of depressive disorders identified that the absence of parental warmth, decreased parental monitoring, over-involvement, increased hostility, high inter-parental conflict, family stress, poor family functioning, maltreatment, neglect, emotional and physical abuse are all factors that may be at play in this environmental association. 1,2,5,33,34 All of these factors require whole family support. Health visiting in the United Kingdom is largely based on mothers and children, with little focus given to fathers in comparison.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into the environmental causes of depressive disorders identified that the absence of parental warmth, decreased parental monitoring, over-involvement, increased hostility, high inter-parental conflict, family stress, poor family functioning, maltreatment, neglect, emotional and physical abuse are all factors that may be at play in this environmental association. 1,2,5,33,34 All of these factors require whole family support. Health visiting in the United Kingdom is largely based on mothers and children, with little focus given to fathers in comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Depression in a parent is a common and potent risk factor for depression in the child 1,2 and is also associated with a range of adverse child health and educational outcomes including poorer academic attainment. 1,38 To date, the vast majority of research has focused on the effect of maternal depression on offspring outcomes. Depression in a mother increases the likelihood of offspring depression by 3 to 4 fold on average, with 6 to 10 fold increases in risk reported when maternal depression is severe or recurrent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression in a parent is a common and potent risk factor for depression in the child [ 1 , 2 ] and is also associated with a range of adverse child health and educational outcomes including poorer academic attainment [ 1 , 3 8 ]. To date, the vast majority of research has focused on the effect of maternal depression on offspring outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Depressive disorders are a prominent cause of disability worldwide [ 10 , 11 ] and often onset in adolescence or early adult life. Early-onset depression (by the 20s) is concerning because numerous studies indicate it is associated with particularly poor outcomes including poor physical and mental health [ 1 , 4 , 5 , 8 ], suicide [ 6 , 7 ] and academic failure [ 12 ]. Educational performance at school is itself also associated with future health and economic outcomes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%